(untitled) (REGE Revista de Gestão, 2023)
Purpose: The present study aims to investigate an unsuccessful implementation of an active learning methodology, that have emerged to improve learning processes and broaden students’ roles in the classroom. Most studies on the subject focus on developing learning strategies based on successful implementations of such methods. Nevertheless, critical reflections on unsuccessful cases might also provide material for developing further contributions to this literature. Design/Methodology/Approach: We conducted an intrinsic case study of an unsuccessful application of the flipped classroom method to an undergraduate basic Statistics course at a Brazilian business school. The data collected comprises the course’s syllabus, evaluation forms, and two rounds of interviews with students and the professor. Findings: Our findings indicate that, apart from what had been mapped by past literature, three additional aspects may limit the chances of successfully implementing a flipped classroom methodology: students’ educational backgrounds, the course’s structural issues, and methodological and relational issues. Originality/value: The present study contributes to the literature on active learning methodologies mainly by mapping additional aspects that should be considered in the implementation of the flipped classroom methodology. Additionally, we investigate an unsuccessful case of such an implementation which is still scant within this literature.